Transfer of founding rights over general hospitals to the Republic of Croatia - Bodul, Dejan (Medicine, law & society, 2024)
The present analysis of the activity of healthcare institutions in recent years shows the fundamental problem of the Croatian healthcare system, which currently faces a deficit of almost two billion euros. The question, therefore, arises as to how the availability, continuity, completeness and solidarity of the healthcare system can be ensured (as the basic principles of the Healthcare Act), taking into account the obligations under the Act on the Execution of the State Budget and the Fiscal Responsibility Act. The aim of this paper is to find an answer to the question of whether the transfer of founding rights over general hospitals to the Republic of Croatia, which is regulated by the Healthcare Act, is constitutionally, legally, and economically justified. The analysis is based on the fact that the issue of healthcare and the organisation of the healthcare system is regulated independently by each country and that this autonomy of the Member States is limited by EU regulations.
Keywords: Croatia; doubts; Healthcare Act; healthcare system; transfer of founding rights